The Global Neighborhood: Programming Initiatives with International Living-Learning Communities - McClanahan, Sarah (Journal of International Students, 2014)
The United States is currently enrolling more international students than any other country in the world. In 2011, approximately 764,000 international students were enrolled in higher education in the U.S., comprising 19% of the world’s total students studying internationally (Institute of International Education, 2012). This rise, as well as the rapid globalization occurring within the United States, has brought about a need for students and staff in higher education to be equipped to communicate cross-culturally and have an understanding of global issues. International living-learning communities (I-LLCs) are a way for universities to provide opportunities for domestic students and international students to live together and gain global knowledge through first-hand experiences and programs directed at international issues. While I-LLCs are not necessarily common across the U.S., many institutions are in the process of creating such programs in order to expand the global focus of their institutions.